Obstetric Outcomes of Eritrean Immigrants in Switzerland: A Comparative Study - Erhardt, Rahel M.; Jafflin, Kristen; Zepro, Nejimu; Abongomera, Charles; Chernet, Afona; Paris, Daniel Henry; Merten, Sonja (International Journal of Public Health, 2024)
Objectives:This study aims to compare obstetric outcomes between Eritrean and Swiss women in Switzerland, focusing on instrumental or surgical interventions and analgesia use.Methods: The study included data from 45'412 Swiss and 1'132 Eritrean women who gave birth in Swiss hospitals (2019)(2020)(2021)(2022). Mixed-effects logistic regression was used to assess the effect of nationality on mode of delivery and analgesia use and multinomial mixed-effects logistic regression to assess the effect of nationality on mode of delivery in women intended for spontaneous vaginal delivery.Results: Compared with Swiss, Eritrean women had a lower rate of primary C-section (Adj. OR 0.73, 95% CI [0.60, 0.89]) but a higher risk of initially planned vaginal deliveries ending in emergency Csection (RRR 1.31, 95% CI [1.05, 1.63]).Eritrean women were less likely to receive epidural analgesia (Adj. OR 0.53, 95% CI [0.45, 0.62]) and more likely to not receive any analgesia (Adj. OR 1.73, 95% CI[1.52, 1.96]).Conclusion: This study reveals disparities in obstetric care, notably in higher emergency C-section rates and lower analgesia use among Eritrean women. For promoting equitable healthcare practices deeper understanding of obstetrics decision-making is needed.